Economic Value Comparation of Situjuah Coffee Farmers on Two Types of Sales in Lima Puluh Kota Regency - Latifa, Dara; Sidqi, Muhammad Syakib; Ispinimiartriani, Ispinimiartriani; Azel, Farid; Gibrand, Khalid Sisri (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2026)
Specialty coffee in Lima Puluh Kota Regency is Situjuah coffee which use two types of sales, namely cherry and green bean forms. This study aims to compare the economic value of coffee farmers who sell Situjuah coffee in 2 forms that affect farmer welfare. The research method uses farm business analysis and comparative analysis of t-tests for comparison of income and labor efficiency. The results of the study showed that the average income received by farmers who sell in the form of green beans earns higher income because the price received is higher than sales in the form of cherries. Although in the identification of farming costs, sales in the form of green beans incur higher farming costs. Comparative analysis shows income in the H1 region with the criteria of a significant difference in the average income of farmers with two types of Situjuah coffee sales. However, the comparison of labor efficiency shows H0 acceptance because there is no significant difference in the two types of Situjuah coffee sales. The difference in average income in the two types of sales resulted in suggestions for farmers to process coffee into green beans to obtain higher economic value because the addition of processing workers did not have an impact on reducing the income of Situjuah coffee farmers. Farmers should also start processing Situjuah specialty coffee in the form of roasted beans and ground coffee in order to increase the price which has implications for improving the welfare of Situjuah specialty coffee farmers.